Estratégias quimiométricas utilizando espectroscopia vibracional e imagens digitais para análise de sal do Himalaia, açúcar mascavo e azeite de dendê - Melo, Welem de Oliveira Santiago de (Universidade Federal de São Carlos, 2025)
Vibrational spectroscopy and digital imaging techniques, when combined with chemometric analysis, are widely applicable in food analysis. The modification of food matrices, whether through derivatization, partitioning, pre-concentration, digestion, drying, or other processes, can help reduce the presence of interfering substances in the samples, thereby improving the analytical performance of vibrational spectroscopy. In this work, 3 applications are proposed: 1) evaluation of commercial Himalayan salt sam-ples using digital imaging, Raman spectroscopy, and pre-extraction of poorly soluble compounds for LIBS analysis; 2) assessment of Raman spectroscopy for detecting adulteration in brown sugar, as well as the potential of FTIR spectroscopy for discriminating samples based on poorly soluble compounds extracted from them; 3) evaluation of commercial palm oil samples by Raman spectroscopy.
Chemometric strategies using vibrational spectroscopy and digital imaging for the analysis of Himalayan salt, brown sugar and palm oil
Keywords: Quimiometria; Espectroscopia vibracional; Imagens digitais; Sal do Himalaia; Açúcar mascavo; Azeite de dendê; Chemometrics; Vibrational spectroscopy; Digital imaging; Himalayan salt; Brown sugar; Palm oil; CIENCIAS EXATAS E DA TERRA::QUIMICA; 9. Indústria, Inovação e Infraestrutura